Reconstruction of the Guilt Concept in the 2023 Indonesian Criminal Code from a Neurolaw Perspective - Kartono Kartono; Sophan Y. Warnasouda; Sri Humana Lagustiani; Soeryaniati Koesoemo; Sri Hastuti; J. Aminullah Alwahdy; Ulang Mangun Sosiawan; Bhanu Prakash Nunna (Unissula, 2026)
This study examines the reconstruction of the guilt concept in the 2023 Indonesian Criminal Code through a neurolaw perspective. Employing doctrinal legal research with an interdisciplinary approach, it analyzes Law Number 1/2023, neurolaw publications from international journals, and recent Supreme Court decisions (2023–2025) through thematic and conceptual analysis. The findings reveal three principal issues. First, Articles 17, 35, 38, and 39 contain progressive provisions but lack neuroscientific specificity, creating interpretive gaps: undefined “ability” (Article 17), unspecified “impairment” threshold (Article 35), and exclusive reliance on traditional psychiatric categories (Articles 38 and 39). Second, analysis of court decisions reveals significant interpretive disparity in cases involving mentally disordered defendants. Neuroscientific evidence demonstrates that prefrontal cortex impairments compromise moral decision-making and impulse control, supporting a spectrum-based understanding of guilt. Third, integrating neurolaw would provide objective criteria for assessing cognitive and volitional capacity across the graded framework of Articles 38 and 39. This study is the first to systematically integrate international neurolaw literature with doctrinal analysis of the 2023 Criminal Code, offering interpretative guidance for key articles and an implementation roadmap for Indonesian criminal justice aligned with the ultimum remedium principle.